PENGARUH TAHAPAN BIOREMEDIASI TERHADAP EFEKTIVITAS ELIMINASI MERKURI (Hg) DI MEDIA CAIR - Liswara Neneng; Nawan Nawan; Asri Adelia (EnviroScienteae, 2023)
Gold miners use mercury for the gold extraction process, and annually releases no less than 1,000 tons of hazardous materials into the environment. The mercury content in the Kahayan watershed reaches 2,996 - 4,687 g/l and this value exceeds the standard limit for mercury content in water. Mercury is highly toxic so that it causes negative impacts on the environment and public health. Bioremediation is one of solution to reduce mercury waste pollution. Mercury bioremediation using microorganisms and adsorbents requires appropriate process steps to be effective in eliminating mercury. This study aims to determine the effect of the bioremediation steps on the effectiveness of mercury (Hg) elimination in liquid media and to determine the most effective bioremediation steps for mercury (Hg) elimination in liquid media. This study used an experimental method with a non-factorial Completely Randomized Design consisting of treatments, namely control (K), treatment 1 (T1), treatment 2 (T2), treatment 3 (T3), treatment 4 (T4), with 5 (five) times repetition. Analysis the results of the bioremediation stage used AAS (Atomic Absorption Spectrophotometry). Data were analyzed using One-way Anova test, LSD test and effectiveness test. The results showed that the bioremediation stage had a significant effect on the effectiveness of mercury (Hg) elimination in liquid media, this was proven by the results of statistical tests carried out using the One-way Anova test and further tests where the different reduction data obtained from each treatment. The initial level mercury 10 ppm, after being given treatment decreased T1 to 1.25 ppm, T2 to 1.33 ppm, T3 to 1.06 ppm, and T4 to 1.24 ppm. The most effective bioremediation step for the elimination of mercury (Hg) in liquid media is the T3 stage starting from Mercury Waste→Microalgae→Bacteria→Red Clay→Activated Charcoal, with a mercury reduction effectiveness value of 89.4%.